Time measuring instruments in sport and physical activities - Aceski, Aleksandar; Tufekchievski, Aleksandar; Vuksanovikj, Vladimir; Spasovska, Katerina (Faculty of physical education sport and health, Skopje, 2019)
Accurate and precise results in the testing and control of the motor skills of athletes, students, recreants, etc. most depend on the choice of appropriate instruments. Time-measuring instruments are often used to estimate the speed capabilities, which can be from the simplest clock, stopwatch to sophisticated photocells.
Keywords: clock; analog; digital; stopwatch; photocells; speed